European readmission policy : third country interests and refugee rights - Coleman, Nils (Immigration and asylum law and policy in Europe ;, 2009)
Offering a comprehensive analysis of readmission agreements, this book examines the intersection of immigration and human rights law and the complex interplay between international, regional and national norms. It makes a robust challenge to prevailing perspectives in legal scholarship and policy on readmission and refugee protection.